2022
DOI: 10.1093/carcin/bgac063
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral microbiota: new frontiers in tumor immunity

Abstract: Microbiota–host interactions are a hot topic of research because of their important role in regulating the malignant transformation of cancer cells and cancer-related immunity. The role of gut microbiota, oral microbiota, and skin microbiota in cancer progression has been extensively studied. However, intratumoral microbiota is a recently discovered topic of research that is still in its infancy. This review focuses on the impact of the intratumoral microbiota on cancer immune responses and highlights how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Numerous literature data suggest that non-nutritious dietary ingredients, such as flavonoids, may affect the composition of the intestinal microbiota [ 319 , 320 , 321 ]. These data emphasize the relationship between flavonoid intake and diverse inflammation-associated chronic conditions such as certain forms of cancers, including colorectal, breast, lung, and liver cancer.…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…Numerous literature data suggest that non-nutritious dietary ingredients, such as flavonoids, may affect the composition of the intestinal microbiota [ 319 , 320 , 321 ]. These data emphasize the relationship between flavonoid intake and diverse inflammation-associated chronic conditions such as certain forms of cancers, including colorectal, breast, lung, and liver cancer.…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…are related to the microbiota disorder in human intestine and other organs ( Xu et al., 2021 ).Zhang et al. indicated that microbiota-host interactions are important in regulating the malignant transformation of cancer cells and cancer-related immunity ( Zhang et al., 2022 ). And Budden showed that chronic respiratory diseases such as asthma, cystic fibrosis and bronchiectasis were associated with changes in microbial diversity or abundance ( Budden et al., 2019 ).Therefore, in our research, we excluded patients who combined with diabetes, autoimmune diseases, tumors and structural lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that diabetes and autoimmune diseases such as systemic lupus erythmatosus, rheumatoid arthritis,etc. are related to the microbiota disorder in human intestine and other organs (Xu et al, 2021).Zhang et al indicated that microbiota-host interactions are important in regulating the malignant transformation of cancer cells and cancer-related immunity (Zhang et al, 2022). And Budden showed that chronic respiratory diseases such as asthma, cystic fibrosis and bronchiectasis were associated with changes in m i c r o b i a l d i v e r s i t y o r a b u n d a n c e ( B u d d e n e t a l .…”
Section: Studies Have Demonstrated That Recurrent Airway Infection Pl...mentioning
confidence: 99%
“…It is worth mentioning that studies have highlighted the role of intratumoral microbiota in cancer initiation, development, immunity, heterogeneity, therapeutic efficacy, and metastatic colonization. [115][116][117][118][119] . Appropriated antibiotic treatment in tumors has been associated with improved prognosis [115] .…”
Section: Givinostat (An Hdac Inhibitor) Was Under Investigation For V...mentioning
confidence: 99%